Association of social network and social support with oral health among institutionalized elderly: A cross-sectional study in Bangalore city - S.S. Neethu; P Puranik Manjunath; R. Yashoda (Elsevier, 2023)
Background: Social relationships in institutionalized elderly are vital for behavioural adaptation to illness as well as for emotional and financial support. There is a need to recognize the influence of social relationships like social network and social support on oral health among institutionalized elderly. The objective of this study was to determine the association of social network, and social support with oral health status among institutionalized elderly. Methodology: A cross-sectional study was conducted among 400 institutionalized elderly aged 60 years and above in Bangalore city. A structured proforma was used to collect data regarding sociodemographic and behavioural factors. Social network and social support were assessed using prevalidated Lubben social network scale and Duke social support index respectively. Oral health status was determined by World Health Organization Oral Health Assessment Form, 2013. Independent t-test, Chi-square test, and logistic regression analysis were performed. A p-value less than 0.05 were considered as significant. Results: The mean age of the participants was 73.5 ± 8.43 years. Inadequate social network and social support were observed in 58.5% and 63% of the institutionalized participants respectively. Social support was significantly associated with caries experience [MT (p < 0.001), FT (p < 0.001), DMFT (p < 0.001), and denture use (p < 0.001). Age greater than 74 years (OR = 1.89, p = 0.009), presence of systemic diseases (OR = 4.12, p < 0.001), low social network (OR = 2.82, p = 0.048), and low social support (OR = 3.59, p = 0.02) were associated with edentulism. Conclusion: Social network and social support were significantly associated with oral health among institutionalized elderly. Hence, strengthening social relationships among the elderly is vital for improving oral health.